Influência dos ácidos graxos da dieta sobre parâmetros de adicção à anfetamina em ratos: aspectos comportamentais, bioquímicos e moleculares - Kuhn, Fábio Teixeira (2015)
Polyunsaturated fatty acids (PUFA) are constituents of neuronal membrane phospholipids which play key roles in the development and functioning of the brain. The last decades have been accompanied by changes in dietary habits, especially in Western countries through the industrialization of foods, which contributed to the increased consumption of trans fatty acids (TFA) and omega-6 fatty acid (FA n-6) over AG omega-3 (n-3). Recent studies of our group have shown that such dietary changes can alter the composition of neuronal membrane phospholipids, altering the dopaminergic system, which may facilitate the preference for psychostimulant addictive drugs. This study was conducted through two experimental protocols: 1) adult Wistar rats were divided into four experimental groups were daily supplemented with soybean oil (SO rich in PUFA n-6), fish oil (FO rich in PUFAs n-3) or hydrogenated vegetable fat (HVF, rich in TFAs) and control group (supplemented with water), from pre-conception period until weaning of the 2nd generation, whose offspring remained the same supplements until 40 post-natal day (PND). Male rats born from the 2nd generation were conditioned in protocol preference with amphetamine (AMPH), and subsequently under behavioral observation rather than for drug development of anxiety, assessment of lipid profile of brain tissue, as well as parameters of stress oxidative the same brain areas; 2) adult Wistar rats, divided into three experimental groups were supplemented daily with a mixture of SO and FO which was generating an ideal ratio of PUFA n-6/n-3 (2:1) or HVF and control group (supplemented with water), since the pre-conceptional period until weaning of 1st generation, whose male pups were kept under the same progenitor supplements until 50 post-natal day when they were submitted to a protocol of self-administration of AMPH, followed by behavioral assessments, analysis and molecular incorporation of FA profile in different brain areas. Animals supplemented by 2nd generation HVF showed incorporation of TFA in whole brain, and increased preference for AMPH, indicating the involvement of changes in dopaminergic circuitry. Animals supplemented with HVF 1st generation had a higher frequency of self-administration of AMPH, indicating greater degree of addiction by psychostimulant. The animals supplemented with HVF in both experimental protocols showed a higher degree of anxiety, the two generations of rats showed increased oxidative status, accompanied by molecular damage in dopaminergic brain areas. The results show that chronic consumption of trans fats at the expense of polyunsaturated fatty acids especially the n-3 series, may modify the constitution of lipid membranes and affect neuronal plasticity, modifying dopaminergic neurotransmission, which is strongly associated with the development of addiction by psychostimulant drugs, and anxiety which is one of the symptoms of AMPHaddiction.